Fuzzy control of an industrial process system using internet and web services, ISSN / e-ISSN ‎1748-5037 / 1748-5045 - Zermane Hanane; Mouss Leila Hayet (International Journal of Industrial and Systems Engineering, 2018)
This paper illustrates an internet-based fuzzy control system of complex industrial manufacturing, which is cement production. It ensures remote and fuzzy control of the process in real time in cement factories in Algeria. The remote control system contains several tasks, such as alarms diagnostic, e-maintenance and synchronising regulation loops, to guarantee the automated performance. To evolve the system, we propose firstly, fuzzy logic to control the cement mill workshop and ensure that the system is operational with minimal downtime. Secondly, we integrate internet technology to remote control via internet to secure human life and render it unnecessary for operators to be at site. When there is a breakdown, it is not necessary to send an expert to diagnose and solve problems. Therefore, the system reduces travel costs by sending reports and transmitting process data. Operators can execute and monitor the system according to authentication access in main control room or via internet.